Functional Assessment of 3D-Printed Multifunction Assistive Hand Device for Chronic Stroke Patients - Zih-Hua Chen; Yun-Lin Yang; Kuang-Wei Lin; Pi-Chang Sun; Chen-Sheng Chen (IEEE Transactions on Neural Systems and Rehabilitation Engineering, 2022)
Patients with chronic stroke often have difficulty opening their hands and performing grasping movements. Several passive hand orthoses for assisting hand rehabilitation have been developed and demonstrated to be clinically effective. However, current devices have several limitations, such as supporting only a single grasping motion and using an abnormal grasping posture. Therefore, this study developed a three-dimensional (3D)-printed multifunctional hand device (3DP-MFHD) to solve these problems and evaluated the feasibility of using the device during home rehabilitation. Six participants were enrolled, and each of them was provided with the 3DP-MFHD. In addition to a task-oriented training course, the participants were asked to train at home for 4 weeks for at least 5 days per week and 40 min per day. The results revealed that hand grip force increased by 36.1%, lateral pinch force increased by 17.6%, and the Action Research Arm Test score increased by 54.1%. The 3DP-MFHD is a promising means to facilitate hand rehabilitation and improve hand strength and function in patients with chronic stroke. The 3DP-MFHD can be used as part of home rehabilitation.